Assessing the Efficacy of Combined Antibiotic Therapy for Recurrent Cystitis in Women - Khurshid, Sana; Ali Raza; Adeel Ahmed; Fareha Mansoor Khan; Jihand Khan; Waqas Ahmed Memon (Medical Journal of South Punjab, 2024)
Objective: The primary aim of this study was to evaluate the curative effects of combination antibiotic therapy in female patients with repetitive cystitis (RC) Methods: A prospective study was conducted at Liaquat National Hospital in Karachi, Pakistan, focusing on women aged between 18 and 50 years with a history of recurrent cystitis who sought medical treatment at the hospital’s outpatient department during the study period. Participants received education on preventive measures against sexually transmitted diseases using the drug cooperation mode of general practice co-operation network. At the clinic, comprehensive clinical and laboratory diagnostics were employed to establish diagnoses, and all participants completed a standardized questionnaire administered by research personnel. Results: In this study, 30 females with recurrent cystitis were enrolled. After receiving a combination of antibiotics, 28 of the participants (90%) experienced complete elimination of their cystitis symptoms, while the remaining 2 (10%) reported only milder symptoms. Conclusion: This study has shown that combined antibiotic therapy is both safe and effective for treating recurrent cystitis in women. Most women experiencing recurrent cystitis find relief from their symptoms with the use of mixed antibiotics.